2007
DOI: 10.1364/oe.15.011883
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the optimum optical incident angle for an imaging acousto-optic tunable filter

Abstract: The selection of the incident polar angle is very important in the entire design of the noncollinear acousto-optic tunable filter (AOTF). The authors discussed how the factors, including tuning range of wavelength, the acoustic frequency, the acousto-optic figure of merit, the spectral bandwidth, the spread of filtered beam and the wavelength dependence, influence the selection of the optimum incident polar angle. By an accurate theoretical analysis, a method of selecting the optimum incident angle was present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The main design method of a noncollinear AOTF was as followed: by the A-O interaction theory, the selection of the incident polar angle θ i was an important and beginning step for the design. The optimum θ i was connected with many factors (such as, the working wavelength range, the acoustic frequency and the power) [11]. As the optical axis was fixed for certain crystal, the direction of the incident light can be got.…”
Section: Design Of the Teo 2 Based Narrow Band Aotfmentioning
confidence: 99%
“…The main design method of a noncollinear AOTF was as followed: by the A-O interaction theory, the selection of the incident polar angle θ i was an important and beginning step for the design. The optimum θ i was connected with many factors (such as, the working wavelength range, the acoustic frequency and the power) [11]. As the optical axis was fixed for certain crystal, the direction of the incident light can be got.…”
Section: Design Of the Teo 2 Based Narrow Band Aotfmentioning
confidence: 99%
“…The acoustic wave can be generated when a radio frequency signal (rf) is applied to a piezoelectric transducer bonded on the birefringent material, so a change in the applied rf produces a variation in the acoustic wave frequency. Previous studies had confirmed that considering the birefringence of the interaction material and its rotatory property was an effective method of increasing the accuracy of the design obviously [4,5]. The spectral resolution is a key index of evaluating the performance of an AOTF for the actual applications.…”
Section: Introductionmentioning
confidence: 99%
“…The spectral resolution is a key index of evaluating the performance of an AOTF for the actual applications. However, the previous expression of the spectral resolution which had been widely used is inaccurate for the neglect of the rotatory property [4][5][6][7]. Thus, in this letter, we give an exact expression of the spectral resolution in order to keep up the higher demand for the accurate evaluation of the performance of AOTF.…”
Section: Introductionmentioning
confidence: 99%
“…This is disadvantageous for improving the performance of the TeO 2 AOTF. In our previous studies, an accurate design theory considering the birefringence and the rotatory property of TeO 2 crystal was put forward, and the significant function of our theory in ensuring the design accuracy had been approved theoretically [18][19][20][21][22]. In this letter, using the accurate design theory, we design a narrow band TeO 2 based AOTF in the visible to the near infrared.…”
Section: Introductionmentioning
confidence: 99%